A novel BCS code in F-OFDM system: a promising candidate for 5G wireless communication systems - Hussain, Ghasan Ali (2021)
Due to the rapid growth in wireless communication systems, Long Term Evolution (LTE), mainly based on Orthogonal Frequency Division Multiplexing (OFDM), no longer meets wireless communication systems request and higher data rate requirements. Thus, to support a number of users, higher throughput, reliability, and lower latency, 5G is a candidate to meet these features. Furthermore, OFDM does not meet the demand of 5G because of its high Out Of Band Emission (OOBE) and Peak to Average Power Ratio (PAPR). Filtered-OFDM (f-OFDM) is considered an alternative waveform for OFDM and a candidate technique for 5G because of its lower OOBE and similar features of familiar OFDM. However, there is a trade-off among reducing OOBE, Bit Error Rate (BER) degradation, and rising PAPR. Therefore, a novel BCS code has been proposed in this thesis for the filtered-OFDM system to improve BER performance with maintaining its low OOBE. It is created using a new methodology that differs from conventional concatenated RS/BCH codes. Hence, an inner RS (7, 1) code has been proposed to achieve compatibility with an outer BCH (15, 5) code and appended by interleaver to create a novel BCS code with low complexity. The results showed that using a novel BCS code in LTE system reduces BER, significantly improved to be better than single and concatenated RS/BCH codes with low decoding complexity. On the other hand, using a novel BCS code in f-OFDM system achieved 0.8dB coding gain at 8×10-3 BER and 1dB coding gain at 2×10-3 BER versus conventional OFDM system in both BPSK and QPSK modulation schemes, respectively. Meanwhile, the proposed system reduced both OOBE and PAPR lower than the conventional OFDM system. In conclusion, due to its low OOBE, improving BER, and minimizing PAPR better than conventional OFDM system, the proposed system is presented as a high competitor candidate of 5G wireless communication systems.